Peran Manusia Sebagai Khalifah dalam Menjaga Lingkungan Hidup Melalui Etika Lingkungan serta Korelasinya dengan Surat Al-A’raf Ayat 56 - Husna, Fitriati; Sarjan, Muhammad (Lembaga Bale Literasi, 2024)
This paper explores the view of the responsibility of the Khalifah on earth in maintaining nature optimally. The sacralization of the universe triggers moral and religious responsibilities among Muslims to care for environmental sustainability. The environment is the place where all the activities of living things in the world take place. Environmental protection is a human job. The environment has a great influence on human life. The environment can change its function due to various factors, one of which is due to the global era. Ecological awareness is very important for people to cope with environmental changes. In addition, the deterioration of natural conditions continues, which is concerning. Ecological awareness can start with the application of environmental ethics. Environmental ethics can be addressed by changing the way we think and live as a whole rather than as individuals. There is a correlation between environmental ethics and the word of Allah SWT in Surah al-Araf verse 56, which prohibits humans from destroying the earth after Allah SWT restores it. The purpose of this study is to explain what is meant by environmental ethics and related issues. And knowing that the correlation between environmental ethics and the synthesis of the Qur'an from the 56 verses of Surah al-Araf is how the people live as the Qur'an.